Bimbingan Zikir Dalam Meningkatkannya Kecerdasan Spiritual Santri Melalui Mujahadah - Hidayatulloh, Agis; Hilman, Fathin Anjani (Irsyad: Jurnal Bimbingan, Penyuluhan, Konseling, dan Psikoterapi Islam, 2023)
Dhikr guidance through the mujahadah program is implemented by the Darussalam Islamic Boarding School to deal with the problems of students who lack spiritual intelligence. So this study aims to determine the implementation process, the supporting and inhibiting factors, and the results obtained from recitation guidance in increasing the spiritual intelligence of students through mujahadah at Darussalam Islamic Boarding School. The method used in this research is the descriptive qualitative method, i.e., a method that will describe or describe the results of a study. The results of this study indicate that the process of remembrance guidance through mujahadah goes through several stages, including tawasulan, material reading, and prayer. The supporting factors are facilities, support from supervisors, guardians of students, and administrators of students, and the inhibiting factors are limited mentors and time. The results are implemented in the daily lives of students, such as empowering their potential, having a clearer vision and mission in life, being more responsible, having a broader meaning of life, increasing the frequency of worship, and having good morals.